Comparison of Passive Construction Kena in Indonesian and Hona in Angkola: X-Bar Theory Analysis - Jamaluddin Nasution; Mulyadi Mulyadi (Budapest International Research and Critics University, 2022)
This study aims to analyze and describe the structure of passive sentences with the construction ofkena in Bahasa Indonesia (BI) and hona in Bahasa Angkola (BA). The theory used is X-bar, which is one of the areas of study in Transformative Generative Grammar examining the structure of phrases. This research is qualitative since it emphasizes the information and data collection in the form of words or pictures in order that it does not emphasize on numbers. The data and data sources in this study are passive sentences BI and BA using the wordkena and hona. The data analysis technique used is the 'agih' technique in which the data analysis method whose determining tool is actually part of the language. Then the sentence as data formed from the data source is analyzed using X-bar theory. The results of this study indicate that the sentence structure in BI is formed with the pattern of Subject + Predicate + Object (SPO) and in BA is Predicate + Object + Subject (POS). The passive has to show the pattern: 1) FI = Spes + I; 2) Spes = NP – N; 3) I = appears/not appear; 4) I = FV + FN; and 5) FV = kena + N. The passive construction hona in BA has the pattern: 1) FI = I + Spes; 2) I = appears/not appear; 3) I = FV + FN; 4) Spes = NP – N; and 5) FV = hona + N. Another conclusion is that the verbkena and hona will always be followed by noun phrase (FN) or noun (N), although it seems that the words appearing afterkena and hona are considered as verb or adjectives.